Over 20‐Year Global Magnetohydrodynamic Simulation of Earth's Magnetosphere - Ilja Honkonen; Max van deKamp; Theresa Hoppe; Kirsti Kauristie (Space Weather)
Abstract We present our approach to modeling over 20 years of the solar wind‐magnetosphere‐ionosphere system using version 5 of the Grand Unified Magnetosphere‐Ionosphere Coupling Simulation (GUMICS‐5). As input we use 16‐s resolution magnetic field and 1‐min plasma measurements by Advanced Composition Explorer satellite from 1998 to 2020. The modeled interval is divided into 28 hr simulations including 4 hr overlap. We use maximum magnetospheric resolution of 0.5 Earth radii (RE) up to about 15 RE from Earth and decreasing resolution further away. In the ionosphere we use a maximum resolution of approximately 100 km poleward of ±58° magnetic latitude and decreasing resolution toward equator. With respect to previous version GUMICS‐4, we have parallelized the magnetosphere of GUMICS‐5 using the Message Passing Interface and have made several improvements which have for example, decreased its numerical diffusion. In total we have performed over 8,000 simulations which have produced over 10,000,000 ionospheric files and 2,000,000 magnetospheric files requiring over 100 TB of disk space. We compare these results to several empirical models and geomagnetic indices derived from ground magnetic field measurements. GUMICS‐5 reproduces observed solar cycle trends in magnetopause stand‐off distance and magnetospheric lobe field strength but consistency in plasma sheet pressure and ionospheric cross‐polar cap potential is lower. Comparisons with geomagnetic indices show better results for Kp index than for auroral electrojet index. Our extensive results can serve, for example, as a foundation for combined physics‐based and black‐box approach to real‐time prediction of near‐Earth space, or as input to other physics‐based models of the inner magnetosphere, upper and middle atmosphere, etc.